LITERATURE REVIEW: EPIDEMIOLOGI KANKER PAYUDARA PENANGGULANGAN DAN UPAYA PENCEGAHAN - Nurfajriah, Nurfajriah; Cahyati, Widya Hary (Jurnal Kesehatan Masyarakat, 2024)
There is an increase in cases of breast cancer in Indonesia until 2023 due to a lack of knowledge related to the prevention and prevention of breast cancer, especially among women. Based on a study conducted by the World Health Organization in 2020, there are 12% of breast cancer, including the most frequently diagnosed type of cancer worldwide. This Literature Review aims to describe the epidemiology of cancer associated with breast prevention and prevention in women. This article uses the Literature Review method based on the latest research articles published from 2013 to 2022. The number of articles reviewed in this literature review is 10 articles. The online-based data source used comes from Indonesia with Google Scholar. Based on the 10 articles analyzed, it was found that respondents who were over 40 years old had a risk of developing breast cancer, compared to respondents who were under 40 years old. Other factors that cause breast cancer to appear are obesity, family history, early menarche, hormonal contraception, age at first birth, parity, and history of breastfeeding. Prevention efforts that need to be done is to do breast cancer screening as early detection of cancer. Treatment that can be done with various therapies and removal of cancerous tissue. It can be concluded that with the knowledge related to the risks that arise due to several factors as a cause of breast cancer and with various prevention efforts that are carried out, it will be able to reduce the number of cases of increasing breast cancer in women.